The Optimum Semen Dilution for the Sperm Quality Index that is Most Predictive of Broiler Breeder Fertility - Parker, H.M.; McDaniel, C.D. (International Journal of Poultry Science, 2004)
The sperm quality index (SQI) can accurately predict overall semen quality and fertility when broiler breeder semen is diluted, at most, 10-fold prior to analysis. The objective of the present study was to determine if a lower semen dilution rate yields an SQI that is an even better predictor of semen quality and fertility when hens are inseminated with a constant volume of semen. Individual ejaculates from 28 males were analyzed for sperm concentration, viability, and the SQI prior to insemination into 15 hens/male. Semen was diluted 2-, 4-, 8-, 10-, and 25-fold prior to analysis for the SQI. The SQI from 25-, 10-, and 8-fold dilutions produced the strongest correlations with total sperm concentration (r = 0.85, 0.82, and 0.80, respectively). Correlation coefficients for live sperm concentration were highest for the SQI from 25-, 10-, 8-, and 4-fold dilutions (r = 0.86, 0.86, 0.83, and 0.73, respectively). Correlation coefficients were similar for the SQI with fertility from the 4-, 8-, and 10-fold dilutions (r = 0.75, 0.72, and 0.72, respectively). It appears that an 8- to 10-fold SQI dilution is the most consistent at predicting fertility and semen quality.